Menyelidiki Kepercayaan dan Praktik Guru EFL Terhadap Penerjemah Untuk Mengajar dan Belajar Bahasa Inggris di Kelas EFL: Penelitian Inkuiri Narasi - Asmara, Nurmaylia Safira; Yanto, Elih Sutisna (Jurnal Ilmiah Wahana Pendidikan, 2024)
There is a significant ongoing discourse in Indonesia over the potential and appropriateness of including both Indonesian and English languages in English as a Foreign Language (EFL) classrooms for instructional purposes. There is a divergence of opinions among educators on the efficacy of utilizing English exclusively in the learning process. Some proponents argue for the effectiveness of this approach, while others advocate for the utilization of many languages, such as translanguaging (Garcia, 2012). The primary objective of this research is to examine the beliefs and practices employed by English as a Foreign Language (EFL) teachers in Indonesia regarding the utilization of translanguaging as a pedagogical tool for English instruction within EFL educational settings. The data was obtained by completing a set of questionnaires and conducting interviews. The present study employs Braun and Clarke's (2006) theme analysis framework, which encompasses six distinct stages. The findings of this study indicate that educators hold the belief that the use of translanguaging can prove advantageous in enhancing language proficiency within English as a Foreign Language (EFL) instructional settings. The findings of this study indicate that two individuals held views favoring translanguaging in the optimal position, while one participant held beliefs favoring translanguaging in the maximal position. Despite the varying positions held by these teachers, they consistently engage in the activity of translanguaging across five distinct segments of the classroom setting (Garcia & Wei, 2014).